Measurement, modelling and evaluation of computing systems : 19th International GI/ITG Conference, MMB 2018, Erlangen, Germany, February 26-28, 2018, Proceedings /: 19th International GI/ITG Conference, MMB 2018, Erlangen, Germany, February 26-28, 2018, Proceedings. (2018) - Unknown
No abstract available